The Challenges of Implementing Robotic Process Automation in Global Business Services - Dahlia Fernandez; Aini Aman (International Journal of Business and Society, 2021)
Organizations use a variety of automation tools to simplify their tasks. One of the tools is Robotic Process Automation (RPA). Recently the issues of the less-than-successful use of the system have been raised. To address this issue, the aim of this study is to understand the challenges of implementing RPA in Global Business Services (GBS) industry. The study is conducted using an in-depth case study approach and interviews at one of the world’s largest oil and gas organizations in the GBS industry. The result of the study showed that the organization is facing various challenges and issues during and after implementing the RPA technology in their organization. Amongst the challenges are the limitation of the task that can be automated, system failure, and safety and data privacy issues. The study suggested that good planning during the implementation of RPA and a strong security team are crucial in solving the challenges faced by the organization.